2007
DOI: 10.1016/j.adolescence.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Urban adolescent stress and hopelessness

Abstract: This study sought to explore potential mechanisms through which uncontrollable, chronic stressors may lead to hopelessness in low‐income, urban adolescents. In particular, the roles of specific coping strategies as moderators and/or mediators of the association between stressors and hopelessness were examined. Results suggest that chronic, uncontrollable stressors were significantly and positively related to hopelessness in this sample. Active coping, distraction coping, and social‐support‐seeking coping emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 86 publications
(127 reference statements)
0
43
1
1
Order By: Relevance
“…Empirical findings on gender differences in the use of active coping have been mixed, with some studies suggesting males are more likely to use this approach (e.g., Landis et al 2007;Kraag et al 2006), others suggesting that females are more likely to use it (Chandra and Batada 2006;D'Imperio et al 2000), and still others reporting no gender differences (Gaylord-Harden et al 2008). Studies of exposure to violence in the context of urban poverty have found that males report more exposure (Buka et al 2001;Carlson and Grant 2008;Foster et al 2004).…”
Section: Potential Role Of Gendermentioning
confidence: 93%
See 1 more Smart Citation
“…Empirical findings on gender differences in the use of active coping have been mixed, with some studies suggesting males are more likely to use this approach (e.g., Landis et al 2007;Kraag et al 2006), others suggesting that females are more likely to use it (Chandra and Batada 2006;D'Imperio et al 2000), and still others reporting no gender differences (Gaylord-Harden et al 2008). Studies of exposure to violence in the context of urban poverty have found that males report more exposure (Buka et al 2001;Carlson and Grant 2008;Foster et al 2004).…”
Section: Potential Role Of Gendermentioning
confidence: 93%
“…Active coping has generally been found to predict fewer symptoms (Aldridge and Roesch 2008;Coyle and Vera 2013;Woodman and Hauser-Cram 2013), but some prior studies have reported that active coping strategies are less effective for coping with uncontrollable stressors (Compas et al 2001;Gonzales et al 2001;Landis et al 2007). In our sample, increasing levels of violence exposure likely indicate decreasing levels of controllability.…”
Section: Tests Of Active Coping and Gender As Moderators Of The Assocmentioning
confidence: 96%
“…For example, Rosario, Salzinger, Feldman, and Ng-Mak (2003) found that active coping in response to exposure to violence predicted increased aggression. Similarly, Landis et al (2007) found that distraction to cope with violence, while often otherwise effective, predicted depression. Two studies have suggested that mild substance use as a coping response is not associated with greater risk in urban populations, even though it has detrimental effects for other populations (Brunswick, Lewis, & Messeril, 1992;Tolan et al, 2002).…”
Section: Stressful Contexts Affect Effectiveness Of Coping Responsesmentioning
confidence: 95%
“…Besides, the hope plays a role as predictive factor of happiness on the Turkish university students. As we mentioned before, previous research findings emphasized that high scores of hope is not only positively related to psychological health (Allott, Loganathan, & Fulford, 2002), psychological strength (Valle, Huebner, & Suldo, 2006), psychological well-being and self compassion (Raque-Bogdan, 2010), self-esteem (Ciarrochi, Heaven, & Davies, 2007), life satisfaction and optimism (Bailey, Eng, Frisch, & Snyder, 2007), but also negatively related to burnout (Pompili et al, 2010), anxiety (Cunningham, Gunn, Alladin, & Cawthorpe, 2008), worry (Shinn et al, 2009), depression (Arnau et al, 2007), stress (Landis et al, 2007), rumination (Michael & Snyder, 2005) and our study results are supported by all these findings. The current study conducted with the Turkish culture also supporting the previous studies.…”
Section: Discussionmentioning
confidence: 99%